PENYULUHAN BAHAYA MEROKOK TERHADAP KESEHATAN DI KELURAHAN RAWA BUAYA JAKARTA BARAT PENYAKIT - Desi Purnamasari (Jurnal Pengabdian Masyarakat Kesosi, 2020)
Indonesia is a developing country that has a high level of consumption and production of cigarettes. In fact, the variety of products and prices of cigarettes in Indonesia has placed Indonesia as one of the largest producers and consumers of cigarettes in the world. Smoking is one of the main risk factors for several chronic diseases that can lead to death. Many studies have proven that smoking can increase the risk of various diseases that can lead to death. This shows that smoking is a major public health problem. Smoking is one of the risk factors for most of the world's deadliest diseases. This community service aims to increase people's knowledge of the dangers of smoking to health. The method used is counseling and lectures by making presentations using Power Point as well as conducting discussions, and asking questions with the extension participants. This community service implementation activity can run well and sustainably.